Two new records of Prochaetoderma Thiele, 1902 (Mollusca, Caudofoveata, Prochaetodermatidae) on bathyal and abyssal bottoms of Galicia, NW Iberian Peninsula - Marcos Pérez Señarís; Oscar García Álvarez; Victoriano Urgorri Carrasco (Nova Acta Científica Compostelana, 2017)
Prochaetodermatidae is one of the three families of class Caudofoveata (Mollusca). It consists of 39 species belonging to a single genus, Prochaetoderma. Only one species of this genus, Prochaetoderma iberogallicum, have been recorded on Galician bottoms, whereas six species are known from the Iberian Peninsula. The external anatomy and the radula of 26 specimens of Prochaetoderma alleni and one of Prochaetoderma gauson are studied in this paper. The specimens were collected during different oceanographic expeditions conducted by the Estación de Bioloxía Mariña da Graña of the Universidade de Santiago de Compostela on bathyal and abyssal bottoms off Galicia. Both species are recorded for the first time on Galician coasts; P. gauson is also a new record for the Iberian Peninsula.